Agglomeration and regional employment growth - Wolfgang Dauth (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2010)
The advent of the New Economic Geography has spawned a renewed interest in questions of agglomeration. The present work expands the research on the impact of agglomeration economies on employment growth by connecting two strands of the empirical literature. A localization index and a cluster index are calculated in order to measure the prevalence of agglomeration. Using these indices, industries and locations that exhibit geographical concentration are identified. The main part of the paper is an econometric analysis. In a dynamic panel data model, the two indices are explicitly used to measure additional dynamic employment growth in agglomerated plants. The study uses panel data that covers all western German employment subject to social security from 1989 to 2006 in 326 districts. I analyze which regional characteristics favor the growth of employment in 191 industries of the manufacturing and service sectors. There is evidence that industrial agglomerations exhibit stronger dynamic growth than other industry/region cells. – – Seit dem Aufkommen der Neuen Ökonomischen Geographie hat auch das Interesse an den Fragen der Agglomeration wieder zugenommen. Die Arbeit erweitert die bestehenden Erkenntnisse über die Auswirkungen von Agglomerationsvorteilen auf das Beschäftigungswachstum, indem sie zwei unterschiedliche Zweige der empirischen Literatur vereint. Zunächst werden ein Lokalisationsmaß und ein Clusterindex berechnet, um die Verbreitung von geographischer Konzentration zu messen. Der Kern des Papiers ist eine ökonometrische Analyse. In einem dynamischen Panelmodell werden diese Indizes explizit genutzt, um das zusätzliche dynamische Beschäftigungswachstum in lokalisierten Wirtschaftszweigen zu messen. Für die Schätzungen wird ein Paneldatensatz mit allen sozialversicherungspflichtig Beschäftigten in Westdeutschland in 326 Landkreisen und kreisfreien Städten über den Zeitraum 1989 bis 2006 verwendet. Anhand dieser Daten wird analysiert, welche regionalen Gegebenheiten das Beschäftigungswachstum in 191 Wirtschaftszweigen des verarbeitenden Gewerbes und des Dienstleistungssektors begünstigen. Die Ergebnisse deuten darauf hin, dass agglomerierte Branchen/Regions-Zellen ein besonders starkes dynamisches Wachstum aufweisen.
Keywords: O47; R11; R12; 330; Employment Growth; MAR Externalities; Jacobs Externalities